Penerapan Metode Luther Sutopo Pada Pengembangan Aplikasi Media Pembelajaran Interaktif Pengenalan Hewan Mamalia - Abdul Aziz, Riyan; Lilik Sugiarto (Politeknik Aceh, 2024)
The learning method that has been used to introduce mammal groups is posters. For children aged four until six years, it is tough to focus on learning to use posters to understand their contents. Interactive learning media is the solution offered by researchers in this study. The method used in this study is the Luther Sutopo method. Interactive learning media for introducing mammals has been successfully created, there are material features in the form of descriptions, food, and audio, and features of audio, video, and image material types that the user can select. The results of the black box test show that all buttons and features can run and are by their respective functions. The results of the distribution to mobile devices, tablets, and laptops did not experience any problems, the application ran well and normally.